In-vitro biocompatibility study of hydroxyapatite coated on Co-Cr-Mo with oxide interlayer - Mas Ayu, Hassan; Izman, Sudin; Daud, Rosdi; Shah, Arman; Anwar, Mahmood; Krishnamurithy, Genasan; Kamarul, Tunku (Penerbit UTM Press, 2017)
The effects of oxide interlayer on cobalt-chromium-molybdenum substrate were investigated in order to improve the quality of hydroxyapatite (HA) coating as well as enhance the cell responses. Substrates were oxidized at temperature of 850 °C and 1050 °C for 3 hours. Oxidized substrates were then coated with HA slurry using dip coating technique. Analysis of surface morphology, thickness and chemical composition of oxide interlayer prior to HA coating were performed using field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy and grazing X-ray diffraction respectively. It seems that rough surface of oxide interlayer provides better mechanical interlocking of HA particles to the substrate surface with no visible micro-cracks. In addition, the HA coated substrates with oxide interlayer also demonstrate strong attachment and better proliferation of cells compared to HA coated substrates without oxide interlayer. The results also demonstrates that cells were spread out more actively as earlier as day 7 and have greater extensions of filopodium on HA coated substrates with oxide interlayer. It is concluded that the introduction of an intermediate oxide layer on Co-Cr-Mo substrate prior to HA coating has shown a positive effect in terms of improving the quality of HA coating as well as cell bioactivity performance.